Treatment of Wide-Neck Intracranial Aneurysm: Current Concepts and Endovascular Approach - Ricky Gusanto Kurniawan; Bambang Tri Prasetyo; Beny Rilianto; Pratiwi Raissa Windiani; Kelvin Theandro Gotama; Abrar Arham (AKSONA, 2023)
Highlight: Endovascular treatment is recommended for aneurysms Wide-neck aneurysm is difficult to treat with endovascular approach. Stent-assisted coiling and flow diverter are choices for wide-neck aneurysms   ABSTRACT A wide-neck aneurysm, described as an aneurysm with a neck of 4 mm or a dome-to-neck ratio of <2, requires more advanced endovascular treatment than a narrow-neck aneurysm. Stent-assisted coiling (SAC) was the sole endovascular approach for wide-neck cerebral aneurysms, which were difficult to treat surgically or by embolization. More advanced endovascular approaches have since been developed in recent years, namely the flow diverter (FD) as an endovascular treatment for wide-neck cerebral aneurysms with an endoluminal reconstruction approach. Both techniques have advantages and disadvantages that must be studied further to develop a wide-neck cerebral aneurysm therapy. Therefore, based on the current literature, this article intends to review the differences in the efficacy and complications of SAC and FD for wide-neck aneurysm therapy.